2022
DOI: 10.1109/access.2022.3202938
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicle Swarm Cooperative Decision-Making for SEAD Mission: A Hierarchical Multiagent Reinforcement Learning Approach

Abstract: Unmanned aerial vehicle (UAV) swarm cooperative decision-making has attracted increasing attentions because of its low-cost, reusable, and distributed characteristics. However, existing non-learningbased methods rely on small-scale, known scenarios, and cannot solve complex multi-agent cooperation problem in large-scale, uncertain scenarios. This paper proposes a hierarchical multi-agent reinforcement learning (HMARL) method to solve the heterogeneous UAV swarm cooperative decision-making problem for the typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The simulation experiments showed that this model could jointly learn the optimal path and jamming power allocation strategy, effectively completing the breach. Yue et al [34] decoupled the coordination decision-making problem of a heterogeneous drone swarm for a suppression of enemy air defense mission divided into two sub-problems and solved them using a hierarchical multi-agent reinforcement learning approach. However, the current application of reinforcement learning in cooperative-jamming resource allocation for multiple jammers still faces challenges such as modeling difficulties and complex reward function design, resulting in poor adaptability to complex adversarial scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation experiments showed that this model could jointly learn the optimal path and jamming power allocation strategy, effectively completing the breach. Yue et al [34] decoupled the coordination decision-making problem of a heterogeneous drone swarm for a suppression of enemy air defense mission divided into two sub-problems and solved them using a hierarchical multi-agent reinforcement learning approach. However, the current application of reinforcement learning in cooperative-jamming resource allocation for multiple jammers still faces challenges such as modeling difficulties and complex reward function design, resulting in poor adaptability to complex adversarial scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al proposed a hierarchical multi-agent reinforcement learning (HMARL) that solves the target assignment problem using a multi-agent deep Q-network (MADQN). The task assignment problem in the execution phase is then solved using independent asynchronous proximal policy optimization (IAPPO) [ 33 ]. Guo et al proposed a multi-agent reinforcement-learning algorithm based on PPO by introducing a centralized training and decentralized execution framework, which can obtain a decentralized policy for each satellite [ 34 ].…”
Section: Introductionmentioning
confidence: 99%